Characteristics and formation mechanism of a heavy air pollution episode caused by biomass burning in Chengdu, Southwest China - Yuan Chen; Xie, Shao-dong (Science of the Total Environment, 2014)
To track the chemical characteristics and formation mechanism of biomass burning pollution, the hourly variations of meteorological factors and pollutant concentrations during a heavy pollution on 18–21 May, 2012 in Chengdu are presented in this study. The episode was the heaviest and most long-lasting pollution event in the historical record of Chengdu caused by a combination of stagnant dispersion conditions and enhanced PM2.5 emission from intensive biomass burning, with peak values surpassing 500 μg m− 3. The event was characterized by three nighttime peaks, relating to the burning practice and decreased boundary layer height at night. The prevailing northeasterly wind during nighttime preferentially brought more pollutants to the urban regions from northern suburbs of Chengdu, where dense fire spots were observed. Due to the obstruction of hilly topography and weak wind speed, minor regional features were reflected from the PM10 variations in nearby cities, whereas the long-distance transport of the plume impacted extensive regions in northern and eastern China. Carbon monoxide (CO) concentrations increased by more than 200%, while exceptionally high PM2.5 levels of 190.1 and 268.4 μg m− 3 on 17 May and 18 May, were observed and showed high correlation with CO (r = 0.75). The relative contribution of biomass burning smoke to organic carbon was estimated from OC/EC ratios (organic carbon/elemental carbon) and elevated to 81.3% during the episode, indicating a significant impact on urban aerosol levels. The occurrence of high PM2.5/PM10 ratios (> 0.80) and K+/EC ratios (> 1.0), along with the increased carbonaceous concentrations and their fraction in PM2.5 (> 40%) and high OC/EC ratios (about 8), could be used as immediate indicators for biomass burning pollution in cities. In addition, the heavy pollution involved a mixture of anthropogenic sources, reflected from the high SOR and NOR values and increases in the EFs (enrichment factors) of Mo, Zn, Cd, and Pb.